The Sociolinguisic Creation of Opposing Representations of Defendants and Victims - Felton Rosulek, Laura (International Journal of Speech, Language and the Law, 2009)
This paper presents a critical analysis of the terms of reference lawyers employ in the closing arguments in criminal trials to create competing representations of the same social actors. Through a systematic discourse analysis of ten closing arguments, I show that the prosecution’s and defense’s differing goals cause them to strategically depict the same defendants, victims, and witnesses in diametrically different manners. Actors who are contrary to an argument are backgrounded or silenced. The two key theoretical constructs then employed by lawyers are personalization and functionalization (van Leeuwen 2002). For example, the defendants, while personalized by the defense, are functionalized by the prosecution, in effect erasing their unique identity except for their role as their person on trial. In sum, I show that through the use of these subtle linguistic tools, lawyers for opposing sides create contrasting representations of the same individuals so that they serve the lawyers’ goals.